Efektivitas Video Edukasi Stroke Terhadap Peningkatan Stroke Literasi Dan Penurunan Post Stroke Depresi Pada Pasien Stroke - Nurhayati, Nurhayati; Roswita, Ria (Politeknik Kementerian Kesehatan Banjarmasin, 2025)
Stroke is a cerebrovascular disease that increases mortality and long-term disability globally. The incidence of stroke in South Kalimantan reaches 12.7% of all stroke incidents in Indonesia. Stroke most often occurs at the age of 55-64 years and 29.5% occurs in people with low education. Patients with post-stroke are very susceptible to post-stroke depression (PSD), To minimize the risk of PSD in non-pharmacological strategies such as increasing literacy, mental and physical health support. Increasing literacy can be done with health education. The design of this study used a quasi-experimental with a pretest-posttest one group test design. The research sample was 20 stroke respondents with a purposive sampling technique. The questionnaire used for stroke literacy used SKAT and PSD used the PHQ-9 questionnaire sheet. The results of this study showed an increase in stroke literacy with a p value of 0.001 and a decrease in PSD with a p value of 0.002.